Redox-Active Poly( l -lysine) as a Cathode toward Sustainable Sodium-Ion Batteries - Bowen Zhao; Chengxiang Chen; Pan Yang; Jinghao Huang; Xiaohao Jia; Yunan Qin; Xiao Zhang; Tao Gao; Fuwu Zhang; Chao Luo (Journal of the American Chemical Society, 2026)
Abstract The advancement of sustainable sodium-ion batteries (SIBs) necessitates cathode materials that exhibit exceptional electrochemical performance and environmentally benign end-of-life degradability. However, achieving this balance remains challenging in degradable material systems due to the intrinsic trade-off between electronic delocalization, ion transport, and structural stability. Here we report a redox-active polypeptide platform featuring a poly(l-lysine) (PLL) scaffold cross-linked with aromatic dianhydrides of varying core sizes. By enabling a “core-size modulation” strategy, this design simultaneously tunes π-conjugation and porosity, thereby coupling electronic delocalization with Na-ion transport and preserving degradability. Consequently, a poly(l-lysine)–perylenetetracarboxylic dianhydride (PLL-PTCDA or P-PT) cathode exhibits a high reversible capacity of 136.8 mAh g–1 at 50 mA g–1 and stable cycling over 15,000 cycles at 1 A g–1. Mechanistic analyses indicate that an increase in the aromatic core size promotes electronic delocalization, while enhanced porosity facilitates Na-ion transport. This combination enables reversible multielectron storage with suppressed dissolution and robust structural integrity. More importantly, the polypeptide scaffold retains intrinsic degradability, enabling chemical or enzymatic degradation once the cathode reaches its end of life. This work establishes a modular molecular-design principle that integrates electrochemical durability with programmed degradability, providing a circular pathway toward lifecycle-aware organic cathodes in next-generation sustainable SIBs.